2021
DOI: 10.25139/jaap.v5i1.3638
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pajak, Tunneling Incentive, Mekanisme Bonus Dan Profitabilitas Terhadap Transfer Pricing

Abstract: Pajak merupakan salah satu sumber penerimaan terbesar bagi negara. Membayar pajak adalah kewajiban yang harus dilakukan baik oleh orang pribadi maupun badan. Perencanaan pajak merupakan cara yang dapat dilakukan untuk dapat mengurangi beban pajak yang dibayarkan, salah satunya yaitu melalui transfer pricing. Akan tetapi, hal tersebut dapat mengurangi pendapatan negara. Penelitian ini bertujuan untuk mengetahui pengaruh Pajak, tunneling incentive, Mekanisme Bonus dan Profitabilitas Terhadap transfer pricing  pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
2
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 0 publications
4
5
2
9
Order By: Relevance
“…Developing countries, including Indonesia, have believed that multinational companies established in Indonesia use the loopholes in existing tax regulations abroad to transfer company revenues and profits abroad through transfer pricing practices in various ways, rebuttals, and justifications for manipulation of these transactions, thereby reducing Indonesia's tax revenues (Saraswati and Sujana, 2017). However, the results of this study are different from the results found by (Purwanto and Tumewu, 2018;Mineri and Paramitha, 2021), who found that taxes did not affect transfer pricing. Thus transfer pricing does not only involve between taxpayers and the tax authorities of a country but also involves two or more tax authorities in different countries.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Developing countries, including Indonesia, have believed that multinational companies established in Indonesia use the loopholes in existing tax regulations abroad to transfer company revenues and profits abroad through transfer pricing practices in various ways, rebuttals, and justifications for manipulation of these transactions, thereby reducing Indonesia's tax revenues (Saraswati and Sujana, 2017). However, the results of this study are different from the results found by (Purwanto and Tumewu, 2018;Mineri and Paramitha, 2021), who found that taxes did not affect transfer pricing. Thus transfer pricing does not only involve between taxpayers and the tax authorities of a country but also involves two or more tax authorities in different countries.…”
Section: Discussioncontrasting
confidence: 99%
“…In an agency relationship, there is a contract of one or more people (principals) that instructs another person (agent) to perform a service on behalf of the principal and authorizes the agent to make the best decision for the principal. The results of this study support the results of research (Saraswati and Sujana, 2017;Rosa et al, 2017;Purwanto and Tumewu, 2018;Sari and Puryandani, 2019;Mineri and Paramitha, 2021), which found that the bonus mechanism had no significant effect on transfer pricing. The company already has a good control system, where all activities carried out must comply with applicable company regulation and are supervised by commitess so that no fraud is commited to maximize company profits in order to obtain large bonuses.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…di luar penerimaan Cukai dan Pajak Perdagangan Internasional (Bea Masuk dan Bea Keluar), (Mineri & Paramitha, 2021;Zainuddin, 2017). Peraturan pajak yang bergerak dinamis pada tahun 2021 menghasilkan HPP (Harmonisasi Peraturan Perpajakan) yang disusun dengan pertimbangan untuk meningkatkan pertumbuhan perekonomian yang berkelanjutan dan mendukung percepatan pemulihan perekonomian, perlunya strategi konsolidasi fiskal yang berfokus pada perbaikan defisit anggaran dan peningkatan rasio pajak yang antara lain dilakukan melalui penerapan kebijakan peningkatan kinerja penerimaan pajak, reformasi administrasi perpajakan, peningkatan basis perpajakan, penciptaan sistem perpajakan yang mengedepankan prinsip keadilan dan kepastian hukum, serta peningkatan kepatuhan sukarela wajib pajak.…”
unclassified